2013
DOI: 10.1016/j.jvs.2013.04.024
|View full text |Cite
|
Sign up to set email alerts
|

Atherectomy offers no benefits over balloon angioplasty in tibial interventions for critical limb ischemia

Abstract: The adjunctive use of atherectomy offered no improvement in primary outcomes over PTA alone in either early or late outcomes in CLI patients who underwent endovascular tibial interventions. Considering the additional cost and increased procedural time, these findings put into question the routine use of adjunctive atherectomy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
52
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(52 citation statements)
references
References 22 publications
(20 reference statements)
0
52
0
Order By: Relevance
“…Furthermore, despite concerns for prolonged procedure times with atherectomy, we demonstrated a shorter procedure duration, similar contrast utilization, and comparable complication rates. As such, atherectomy may prove to be important in BTK revascularization as an adjunctive therapy to PTA or DCB angioplasty pending adequately power randomized trials with relevant clinical outcomes.…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…Furthermore, despite concerns for prolonged procedure times with atherectomy, we demonstrated a shorter procedure duration, similar contrast utilization, and comparable complication rates. As such, atherectomy may prove to be important in BTK revascularization as an adjunctive therapy to PTA or DCB angioplasty pending adequately power randomized trials with relevant clinical outcomes.…”
Section: Discussionmentioning
confidence: 76%
“…The small CALCIUM 360 pilot trial ( n = 50) revealed no significant difference in target vessel revascularization or amputation at 1 year . A retrospective single‐center study of 418 tibial interventions (19% atherectomy) in patients with CLI showed no improvement in primary patency nor limb salvage at 12 and 36 months . Both study results need to be interpreted with caution given the small number of atherectomy patients and/or lack of randomization; however, these studies contribute to the current clinical equipoise.…”
Section: Discussionmentioning
confidence: 94%
“…Definitive clinical benefit of atherectomy over PTA is not clear. A retrospective study of 418 tibial interventions for CLI found no benefit over PTA, and this study used variety of atherectomy devices including directional, orbital and laser [88].…”
Section: Atherectomymentioning
confidence: 95%
“…Procedures were mainly performed for CLI treatment. According to Kaplan–Meier analysis, there was no difference at 12- and 36-month follow-up in primary patency (69, 55% vs. 61, 46%; p  = 0.158), assisted primary patency (83, 71% vs. 85, 67%; p  = 0.801), limb salvage (79, 70% vs. 81, 77%; p  = 0.485) and survival (77, 56% vs. 80, 50%; p  = 0.944) between balloon angioplasty and atherectomy-assisted group [33]. …”
Section: Multicenter Prospective Registries and Large Retrospective Cmentioning
confidence: 99%